Pengaruh Pendayagunaan Zakat Produktif Terhadap Kesejahteraan Mustahik: Studi Badan Amil Zakat Nasional Kabupaten Sorong - Dini Patharani; Rusdi Rasyid; Arfandi Arfandi (Prodi Ekonomi Syariah IAIN Sorong, 2022)
Economy issues often associated with poverty. Plus with covid-19 pandemic that gives plenty of huge impact for economy one of them is the decrease of UMKM productivity and decrease in people’s income. Therefore, it needs both the effort and the role of various parties to overcome the poverty and the economy issues. With the existence of a Productive Zakat Fund program utilization provided by the Badan Amil Zakat Nasional of Sorong Regency is expected to optimize zakat funds through business capital assistance so that it can affect the welfare of Mustahik in Sorong Regency and reduce the poverty. The purpose of this study is to determine the effect of independent variable (X) which is the utilization of productive zakat on the dependent variable (Y) the walfare if mustahik at BAZNAS Sorong Regency. The type of this research method is quantitative. Data collection technic in this research is interview and documentation. The method of data analysis in this research used SPSS 25. The result showed that productive zakat given to mustahik had a positive and significant effect on the welfare of mustahik. Thican be seen in the hypothesis testing tcount> ttable, namely (3.111> 2.024) and the significance value is 0.004 <0.05, which means that the hypothesis H1 is accepted and there is significant effect of the utilization of productive zakat on the welfare of Mustahik at BAZNAS Sorong Regency.